Bases genéticas del desarrollo y composición de la cutícula del fruto de tomate - Barraj, Rida (UMA Editorial, 2022)
The plant cuticle, as the interface between the plant and the environment, plays an important role in plant performance, fruit quality and postharvest. Plant cuticles show compositional and structural variability among and within species and also between organs of the same species. It is composed by a cutin polymer matrix with waxes that can be accumulated on the surface (epicuticular waxes) or embedded in the matrix (intracuticular waxes), phenolics and polysaccharides from the cell wall. In tomato fruit cuticle, the phenolic fraction is a characteristic component and is the main modulator of the cuticle’s stiffness, deformation and strength. This phenolic domain is composed of cinnamic acids derivatives present during fruit growth and increases significantly during ripening with the incorporation of the flavonoid naringenin chalcone, responsible for the yellow-orange color of the cuticle in red ripe tomatoes. Understanding the genetic basis of cuticle composition and color is needed for breeding in crop species. Little is known about the range and the genetic bases of naturally occurring variation for cuticle composition and structure in tomato. The general objective of this work is to dissect the genetic architecture underlying these variations and to exploit available natural genetic diversity in wild species to transfer the beneficial alleles affecting cuticle-associated traits to commercial varieties. In this work, we have explored for the first time the cuticle variability of red-fruited species in two mapping populations derived from the interspecific cross between the domesticated tomato (Solanum lycopersicum L.) and its closest wild relative Solanum pimpinellifolium L., a Recombinant Inbred Line population and an Introgression Line population. Quantitative trait locus (QTL) analyses were conducted to investigate tomato fruit cuticle components and color traits.
Genetics of tomato fruit cuticle development and composition
A total of 60 QTLs were identified, indicating that all the cuticle traits analyzed have a complex polygenic nature. A combination of additive and epistatic interactions was observed for all the traits, with positive contribution of either both parental lines to most of them. Colocalization of QTLs for various traits uncovered novel genomic regions producing extensive changes in the cuticle composition and color. Two genomic regions, located in chromosomes 1 and 12, were found to be responsible for the negative relationship between cuticle waxes and phenolics percentage contents. Several candidate genes, including transcription factors and structural genes, are postulated and their expression analyzed throughout development. We also pyramided several of the phenolic content-related QTLs from the S. pimpinellifolium accession into the genetic background of the cultivated tomato with the aid of single nucleotide polymorphisms (SNP) molecular markers, polymorphic between both parental lines. Our pyramiding strategy resulted in 23 new introgression lines, combining more than one QTL for cuticle phenolics in the genetic background of the cultivated tomato to produce new genetic materials with higher or lesser cuticle flavonoid content. The interactions between the combined QTLs were also dissected and the interactions, either additive or epistatic, of each created combination was identified. Accumulation of phenolics QTLs was only partially effective in reducing phenolics in the cuticle since no QTL-combined line showed phenolic content comparable to that of TO-937. Results of pyramided QTLs emphasized that the genetic control of phenolics-related traits was very complex, and epistatic interactions changed the expected outcome of several of the QTLs depending on the specific alleles of the combined QTLs.
Keywords: Biología molecular; Bioquímica; Universidad de Málaga - Tesis doctorales; Tomates; Cutícula vegetal; Flavonoides; Tomato; QTL; Cuticle; Flavonoids